Material selection for enhanced performance in anion exchange membrane water electrolyzers: a study of membranes and gaskets - Singh, Kailash; Selvaraj, Kaliaperumal (Industrial & Engineering Chemistry Research, 2025)
Anion exchange membrane water electrolyzer (AEMWE) is an emerging technology for large-scale hydrogen production, where membrane electrode assembly (MEA) plays a critical role in the electrolyzer efficiency. This study investigates the effects of different membranes (Piperion, Aemion, and Sustainion) and gaskets (Viton, poly(tetrafluoroethylene) (PTFE), and Silicon) using a non-platinum group metal (non-PGM) bifunctional electrocatalyst under fixed compression and flow rates. Membrane properties such as ionic resistance and diffusion and gasket properties like thermal suitability and compressibility significantly affect the overall performance of AEMWE. The results indicate that Sustainion and Aemion membranes are best suited for lab-scale and industrial applications, respectively, while Silicon and PTFE gaskets are optimal for corresponding scales. Understanding these effects can help to improve the efficiency and guide material selection. This study provides valuable insights for researchers developing AEMWE technology, enabling advancements from laboratory research to megawatt-level industrial hydrogen production and supporting the transition to clean-energy solutions.